EFEKTIVITAS MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU SLB MUARO JAMBI - Dedy Alamsyah; A Khalik; Dian Nisa Istofa (JMiE (Journal of Management in Education), 2020)
This study aims to analyze the efficiency of human resource management in improving the quality of Muaro Jambi Extraordinary School. This study uses qualitative descriptive methods. Data is collected through observations, interviews, and documentation. The results showed that SLB Muaro Jambi applies two management functions in managing its SDM, namely the planning and implementation functions. Human Resource Management consists of planning the needs and development of educators and education personnel; procurement of capacity building training for teachers and staff/employees. The implementation of human resources involves committees, teachers, and staff/ employees to realize the activities that have been planned. Human Resources Management can effectively improve the quality of education in SLB.